ANALISIS HUBUNGAN ANTARA PERTUMBUHAN DAN PEMERATAAN DALAM KEBIJAKAN DESENTRALISASI DI INDONESIA TAHUN 1995-2007 - Grisvia Agustin (Trunojoyo University of Madura, 2009)
This research analyzes potential trade-off between economic growth and regional equity in the design of fiscal decentralization. A theoritical model of fiscal decentralization is being used, where overall national economic growth and regional equity in the regional distribution of fiscal resources are two objective pursued by a benevolent policy maker. Solutions that emphasize regional equity tend to have larger central government expenditures and higher contribution to the central budget by richer juridictions. The reserve is true for solutions emphasizing growth. The model is tested using Generalized Least Square (GLS). Fiscal decentralization in Indonesia led to significant increases in regional equity.